Biodegradation of acenapthene and naphthalene by Pseudomonas mendocina: Process optimization, and toxicity evaluation. Issue 5 (October 2017) - Barman, Shramana Roy; Banerjee, Priya; Mukhopadhayay, Aniruddha; Das, Papita
Highlights: First report of biodegradation of two PAHs with Pseudomonas mendocina . ∼99% Removal of both acenapthene and naphthalene respectively was achieved. RSM optimization reduced cost and time required for total study. Toxicity analysis revealed benign and ecofriendly nature of treated solutions. Results established biodegradation as an efficient approach for PAH removal. Abstract: Removal of poly aromatic hydrocarbons (PAHs) from waste water is a challenging task due to their hydrophobic and persistent nature. The present study investigated the efficiency of Pseudomonas mendocina for PAH biodegradation. Biodegradation of PAHs acenapthene and naphthalene was studied and the process was optimized with the Central Composite Design (CCD) feature of Response Surface Methodology (RSM). Toxicity analysis of the untreated and bio treated solutions were conducted on a comparative scale using Cicer arietinum (chickpea) in terms of oxidative stress, germination studies and biochemical parameters. Almost 98.8% and 98.6% degradation of acenaphthene and naphthalene respectively by Pseudomonas mendocina was recorded under RSM optimized conditions. Results of the toxicity analysis further indicated that the bio-treated solutions were fit to be reused or discharged, thereby establishing the potential of Pseudomonas mendocina for biodegradation applications in wide scale.